2014
DOI: 10.1155/2014/480170
|View full text |Cite
|
Sign up to set email alerts
|

Safe-Site Effects on Rhizosphere Bacterial Communities in a High-Altitude Alpine Environment

Abstract: The rhizosphere effect on bacterial communities associated with three floristic communities (RW, FI, and M sites) which differed for the developmental stages was studied in a high-altitude alpine ecosystem. RW site was an early developmental stage, FI was an intermediate stage, M was a later more matured stage. The N and C contents in the soils confirmed a different developmental stage with a kind of gradient from the unvegetated bare soil (BS) site through RW, FI up to M site. The floristic communities were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…On the contrary, Cui et al (2019) investigated the rhizosphere soil microbial communities of Abies fabri along an altitudinal gradient below the timberline at the Tibetan Plateau and found that microbial communities varied significantly with altitude but not between the rhizosphere and bulk soil. Nevertheless, it was reported that despite the harsh environmental and physical conditions plants select specific communities (Ciccazzo et al, 2014). In our investigation, the influence of rhizosphere weakened the significant impact of altitude on prokaryotes, which was not the case for fungi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, Cui et al (2019) investigated the rhizosphere soil microbial communities of Abies fabri along an altitudinal gradient below the timberline at the Tibetan Plateau and found that microbial communities varied significantly with altitude but not between the rhizosphere and bulk soil. Nevertheless, it was reported that despite the harsh environmental and physical conditions plants select specific communities (Ciccazzo et al, 2014). In our investigation, the influence of rhizosphere weakened the significant impact of altitude on prokaryotes, which was not the case for fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Coarse-textured soils with shallow horizons and a low water retention capacity do not protect against environmental stressors (e.g., temperature and moisture fluctuations). Despite the harsh conditions in (high) alpine ecosystems, mountain soils are places of considerable microbial diversities distinctly shaped by the environmental factors (Ciccazzo et al, 2014; Rime et al, 2015). Contrarily to the latitudinal gradients investigated in arctic ecosystems, studies in the alpine and nival zones of mountain environments are conducted along altitudinal transects, thereby addressing the influence of altitude-dependent climatic and biotic variations on microbial species distribution and functional diversity (Bryant et al, 2008; Fierer et al, 2011; Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their ability to respond quickly to environmental changes, microorganisms are efficient bioindicators of soil biological characteristics 14 15 . Numerous studies have shown that changes in the size and activity of the soil microbial community are major contributors to soil degradation caused by agricultural management 16 17 18 . Soil organisms play important roles in maintaining soil health and quality and soil nutrient biogeochemical cycling, particularly in N transformation 19 20 21 .…”
mentioning
confidence: 99%
“…The changes in the microenvironment of the sediment can also make ecological ditches more suitable for microbial reproduction. The number of many bacteria has increased significantly, especially the Proteobacteria in which the degradation process of some pollutants, biological denitrification, and P removal play a central role [27]; this makes ecological ditches more conducive to the purification effect of microorganisms on the N and P pollutants in the water [28]. Of course, we also got some unexpected results.…”
Section: Discussionmentioning
confidence: 99%